MORPHOLOGICAL CHANGES IN RAT HEART MUSCLE IN EXPERIMENTAL PERITONITIS AGAINST THE BACKGROUND OF DIABETES MELLITUS - Dzyubanovskyi, I.Ya.; Vervega, B.M.; Pidruchna, S.R.; Melnyk, N.A. (World of Medicine and Biology, 2020)
The purpose of the work was to study the morphological changes in the heart muscle of rats with modeled acute peritonitis against the background of diabetes mellitus compared to animals with experimental widespread acute peritonitis. Structural changes of cardiomyocytes (focal intracellular myocytolysis and pycnotically altered nuclei), pronounced perivascular edema, focal dystrophic-necrotic changes, polymorphocellular infiltrates, which were located in the stroma, perivascularly and around the necrotically altered cardiomyocytes, were revealed. Structural changes of cardiomyocytes and disturbances in all links of the microhemocirculatory bed, which were manifested in dystonia and paresis of vessels, changes in rheological properties of blood were more pronounced in the conditions of comorbid pathology.
Keywords: acute peritonitis; diabetes mellitus; morphological changes of the heart muscle